EFFECT OF TAX REFORMS ON HOSPITALITY & TOURISM INDUSTRY IN JAIPUR - A STUDY - Srivastava Manoj, Bhattacharya G, Kaikini Ravindra, Mathur Vishal, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study has been undertaken to investigate the effect of GST on the Jaipur tourism industry and the variables on which the introduction of GST had changes the business operations in Jaipur. The research has been done through primary data from the source of the city of Jaipur and have taken the responses of businesses and tourism company owners to rule out if there was any impact of GST after its introduction in 2017. Goods and Services Tax reforms is one of the major reforms till date India post-Independence. It is a unified single-tax applied on the supply of goods and services from the manufacturer to the consumer. As the Indian hotel industry is one of the rapidly growing sectors in the economy, contributing around 6.23% of the national GDP and 8.78 percent of the national employment total. A month after the introduction of GST, Ganesh Shetty, President of Restaurants and Hoteliers Association, Pune, said that the businesses in hotels across India had come down by 20%. He further stated that the hotels were incurring high costs in terms of the up gradation of IT infrastructure, training of personnel and hiring of experts for compliance with the new system of GST. The consumers also complained about the increase in their restaurant bills and have stated that their bills are more than the earlier regime. In this context, this study was undertaken to identification of the problems as well as the prospects of the impact of GST reforms on Hotel Industry in Jaipur. The study revealed that the hoteliers faced problems in transitioning to the new system, their compliance costs rose leading to a general increase in the cost of goods and services for the consumer. However, it is expected that in the long run GST will prove beneficial and make the dream of One Nation One Tax come true.